Game Theory - Crisis Management Tool for Creation Security Policies - Fuka Jan; Obršálová Ilona; Jelínková Lucie; Slavíček Ondřej (My University, 2016)
Issue of terrorism and national, regional or private company security policies are becoming still more important part of security strategies and crisis management worldwide. Czech Republic is state that would not be actually threatened by international terrorism, but prevailing security situation poses number of challenges and especially Czech domestic extremism and terrorism should be considered as significant security threat. Problem of extremist and terrorist activities is increasingly studied using Game Theory, which seems to be proper instrument of crisis management in case when it is not possible to examine various conflict participants, without consideration of their reaction and interaction. This work deals with the Czech extremist and terrorist scene as a potential threat for the Czech state. In this article is analysis of Czech terrorist scene, on the basis of which is designed the direction in which it is possible to proceed in the case of using Game Theory. Solutions for private and mainly public sector are therefore based on available information obtained by analysing domestic extremism and terrorism, and description of Czech public administration. It can be assumed that the framework related to Czech conditions would be possible to use in larger or smaller modifications in other states of European Union.
Teorie her - Nástroj krizového managementu pro tvorbu bezpečnostních politik
Keywords: crisis, extremism, Game Theory, region, management, public administration, terrorism; krize, extremismus, Teorie her, region, správa, veřejná správa, terorismus